PEMANFAATAN VIDEO PODCAST ISLAMI SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN ISLAM ERA DIGITAL - Elvy Gustina; Supratman Zakir (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This study aims to thoroughly examine the utilization of Islamic video podcasts as a learning media for Islamic Religious Education (PAI) in the digital era. The background of this research is based on the rapid development of information technology, which demands innovation in religious learning strategies to enhance the relevance and effectiveness of the educational process. The study employs a library research method with a qualitative descriptive approach, where data is collected from various relevant literature sources and analyzed using systematic content analysis techniques. The findings indicate that Islamic video podcasts have significant advantages in terms of accessibility, interactivity, and audiovisual appeal that can support PAI learning more effectively. However, its implementation still faces several challenges, including limited teacher competencies in digital literacy, inadequate technological infrastructure, and the need for content moderation to align with moderate and inclusive Islamic values. The implications call for the development of an adaptive curriculum and continuous strengthening of teacher professionalism as efforts to support the optimal use of this media in PAI learning. This research provides a comprehensive conceptual contribution as a foundation for developing relevant and sustainable learning media innovations in religious education.